Tailoring of alginate-gelatin microspheres properties for oral Ciprofloxacin-controlled release against Pseudomonas aeruginosa - Islan, Germán Abel (2014)
Context: Ciprofloxacin (Cip) is a broad spectrum antibiotic frequently used in the treatment of infectious diseases caused by Pseudomonas aeruginosa. Cip oral administration is commonly associated with poor drug biodisponibility, gastrointestinal tract irritation, and toxic undesirable side effects. Objective: The aim of this work is to provide an oral biopolymeric system for controlled release of Cip. Materials and methods: Alginate-gelatin blend microspheres were crosslinked in the presence of 1,2-propylene glycol, calcium, and glutaraldehyde. Studies of Cip encapsulation and release were performed. Matrix characteristics were studied simultaneously by optical microscopy and Fourier transform infrared spectroscopy (FTIR) using synchrotron light, and by texturometric analysis. Microsphere surface topologies were observed by scanning electron microscopy (SEM), atomic force microscopy (AFM), and epifluorescence microscopy. Results: Microspheres crosslinked with glutaraldehyde showed about 80% Cip encapsulation and less than 10% Cip release under simulated gastric conditions in 15min, while a controlled release profile was observed at intestinal environment conditions. Antimicrobial activity against P. aeruginosa showed an increasing bacterial growth inhibition in time. Finally, bovine serum albumin (BSA) was used as model protein for binding of macromolecules onto active surface of microspheres, with a consequently modulation of Cip release. Discussion and conclusions: The results are indicating that alginate/gelatin matrix crosslinked via Ca2+ and glutaraldehyde can be tailored by decorating the microsphere surface with biological active molecules useful for targeting, making a potential tool to improve Cip oral administration for infection diseases.